Estimated effects of climate and imidacloprid use on the abundances of woodland salamanders - John C. Maerz; Jade A. Samples; Danielle R. Bradke; Cheyana Bassham; James A. Martin; Jeffrey Hepinstall-Cymerman; Anthony F. Lagalante; Elizabeth McCarty (Forest Ecology and Management, 2026)

Innovative and practical tools for monitoring and assessing biodiversity status and impacts of multiple human pressures in marine systems - Angel Borja; Torsten Berg; Hege Gundersen; Anders Gjørwad Hagen; Kasper Hancke; Samuli Korpinen; Miguel C. Leal; Tiziana Luisetti; Iratxe Menchaca; Ciaran Murray; GerJan Piet; Sophie Pitois; et al. (Environmental Monitoring and Assessment, 2024)

Resiliency of Nuttall oak but not Shumard oak to winter and spring flood: dormancy alone does not confer flood tolerance - Richard D. Sample; James Cook; Benjamin A. Babst (Trees, 2023)

Ecosystem service flows from a migratory species: Spatial subsidies of the northern pintail - Kenneth J. Bagstad; Darius J. Semmens; James E. Diffendorfer; Brady J. Mattsson; James Dubovsky; Wayne E. Thogmartin; Ruscena Wiederholt; John Loomis; Joanna A. Bieri; Christine Sample; Joshua Goldstein; Laura López-Hoffman (Ambio, 2019)

Experimental infection of laboratory-bred bank voles (Myodes glareolus) with murid herpesvirus 4 - David J. Hughes; Anja Kipar; Gail Leeming; Jeffery T. Sample; James P. Stewart (Archives of Virology, 2012)

CTCF and Sp1 interact with the Murine gammaherpesvirus 68 internal repeat elements - Hannah C. Stevens; Kevin S-W Cham; David J. Hughes; Ren Sun; Jeffery T. Sample; Vivien J. Bubb; James P. Stewart; John P. Quinn (Virus Genes, 2012)

An ancient linked fluid migration system: cold-seep deposits and sandstone intrusions in the Panoche Hills, California, USA - Hilde Schwartz; James Sample; Kevin D. Weberling; Daniel Minisini; J. Casey Moore (Geo-Marine Letters, 2003)

Forestry Education: Adapting to the Changing Demands on Professionals - V. Alaric Sample; Paul C. Ringgold; Nadine E. Block; James W. Giltmier (Journal of Forestry, 1999)
Recent evolution in the practice of forestry can be linked to changes in the public's perception of sustainability and to developments in science, communications, and global markets. In response, when hiring graduates of professional forestry programs, forestry employers have changed the set of skills and competencies sought. A nationwide survey of forestry employers, educators, and recent graduates, conducted to assess how well US forestry programs are preparing professionals to practice forestry today, reveals some discrepancies between what employers want and what the schools provide. External financial and political pressures on higher education make it difficult for educators to close these gaps, but opportunities exist for employers to help.

Third-Party, Performance-Based Certification: What Public Forestland Managers Should Know - Catherine M. Mater; V. Alaric Sample; James R. Grace; Gerald A. Rose (Journal of Forestry, 1999)
Two state forests and one county forest have completed pilot programs testing verification of sustainable forest management by outside organizations. Among other goals, each agency wanted to assure citizens that their forests were well managed and to create models for nonindustrial private forestlands. All three agencies' performance was certified, and areas marked for improvement had already by targeted by staff. The certifed then evaluated the certifiers and found them generally professional and technically competent, if occasionally unrealistic. Reaction from environmental organizations, which are cautious about promoting certification for public lands, has been mixed.